Characteristics of Students In Resolving Word Problems Based on Gender - Fatqurhohman Fatqurhohman (Journal of Education and Learning Mathematics Research (JELMaR), 2021)
This study aims to analyze student errors in resolving word problems, which are then formulated into characteristics of student errors according to gender. The subject selection was done randomly from male and female students of grade VII who made mistakes in solving the questions. Research data from the test results of 2 items word problem type. The form of student error is based on misconceptions, procedures, and techniques. The results showed the students' misconceptions, don’t understand question commands, do not write information correctly, misinterpret question information, do not simplify fractions correctly, do not understand the value of fractions, misunderstand number signs/symbols and do not understand number signs/symbols, incorrectly determine signs/symbols of operations. Procedural error, incorrectly determining the settlement operation Technical errors, incorrectly using calculation operation marks, incorrectly performing calculation operations, incomplete settlement steps, incomplete simplification, incorrect simplification. Technical errors, namely calculations are not in accordance with the command, less careful (careless) writing answers, errors in writing answers and it do not match the command questions (conclusion). The reason is not understanding the reading and not being familiar with the questions. Students' understanding and knowledge of reading have an important role in identifying, interpreting, and even selecting or determining completion strategies.